Association between telomere length and erectile dysfunction: a cross-sectional study - Chen, Xiaobao; Liu, Binhong; Zhou, Junkai; Lin, Junwei; Jiang, Wei; Xie, Ruoyun (Frontiers in Endocrinology, 2024)
Background: Leukocyte telomere length (LTL) serves as a significant biomarker of aging. Erectile dysfunction (ED) is a commonly observed condition among middle-aged and older men. The objective of this study is to explore the potential association between LTL and ED.We utilized data from the National Health and Nutrition Examination Survey (NHANES) to examine the association between LTL and ED. Weighted multivariate regression analyses were performed as the primary statistical method. Subgroup analyses were conducted to investigate specific population subsets, and restricted cubic spline (RCS) analyses were employed to assess the non-linear relationship between LTL and ED.The results of weighted multivariate regression analyses revealed a negative correlation between LTL and the risk of ED. Individuals with ED exhibited shorter LTL compared to those without ED. For each unit increase in LTL , there was a 54% reduction in the risk of ED (odds ratios[OR] 0.46, 95% confidence intervals[CI] 0.25-0.85). When LTL was considered as a categorical variable, the group with the longest LTL (Q5) had a 44% lower risk of ED compared to the group with the shortest LTL(Q1) (OR 0.56, 95% CI 0.39-0.81). A non-linear relationship was observed between TL and ED. Various sensitivity analyses were conducted to validate the stability of the results, and consistent findings were obtained.The negative association between leukocyte LTL and ED suggests that delaying the shortening of LTL may decrease the risk of ED.